Techniques and methods for monitoring the evolution of upper limb fine motor skills : literature review - Guzmán Villamarín, Juan David; Guzmán Villamarín, Diego Enrique; Rengifo Rodas, Carlos Felipe; Londoño Prieto, Jerónimo (Ingeniería Solidaria, 2019)
Introduction: This review article is the product of research on the methods, techniques and devices used in the measurement of fine motor skills of upper limbs and its respective evolution, developed at Universidad del Cauca in 2018. Problem: Objective measurement of the evolution of upper limb motor skills in the rehabilitation processes. Objective: To identify the conventional techniques and electronic devices used in the measurement of the evolution of upper limb motor ability. Methodology: Four scientific databases were reviewed in addition to the Google Scholar search engine. The keywords used for the search were: "fine motor skills", "hand measurement", "hand rehabilitation"and "hand function", among others. Results: Approximately 3840 articles related to the subject were found. When applying the exclusion criteria, the article number to be revised was reduced to 63, which were analyzed in the present review. Conclusions: The tools applied by health professionals are convenient due to their rapid execution and easy access, however they can be subject to human error since they depend on the experience of the user. Electronic systems present objective measurements, however, their complexity and cost are high. Originality: This work presents information on the therapeutic techniques and technological devices used, in certain pathologies, for the evaluation of upper limb motor ability. Limitations: Not all articles analyzed have a detailed description of the people in which the studies were conducted.